Mexican species of the genus Orthocentrus (Hymenoptera, Ichneumonidae: Orthocentrinae) - Humala, Andrei E. (Zootaxa, 2019)
The Mexican species of the genus Orthocentrus Gravenhorst are reviewed. Fortytwo species of the genus Orthocentrus are described as new: O. areolatus sp. nov., O. aztecus sp. nov., O. brevicornis sp. nov., O. collaris sp. nov., O. contrerasi sp. nov., O. coronadoae sp. nov., O. dorsofuscus sp. nov., O. elongatus sp. nov., O. flavoorbitalis sp. nov., O. fuscipes sp. nov., O. hidalgoensis sp. nov., O. kasparyani sp. nov., O. khalaimi sp. nov., O. latus sp. nov., O. longiventris sp. nov., O. lopezi sp. nov., O. lostuxtlasi sp. nov., O. malaris sp. nov., O. mexicanus sp. nov., O. microphthalmus sp. nov., O. minor sp. nov., O. montanus sp. nov., O. montezuma sp. nov., O. oaxacae sp. nov., O. ocampo sp. nov., O. pictus sp. nov., O. podagricus sp. nov., O. rhombifer sp. nov., O. rufipleuris sp. nov., O. ruizi sp. nov., O. scabrosus sp. nov., O. scutellatus sp. nov., O. sierrae sp. nov., O. similis sp. nov., O. tamaulipecus sp. nov., O. tergalis sp. nov., O. tlaxcalensis sp. nov., O. ungularis sp. nov., O. varicolor sp. nov., O. veracruzus sp. nov., O. vulgaris sp. nov., O. zaldivari sp. nov. In total, 53 Orthocentrus species are now known to occur in Mexico, and 52 species are reported from Mexico for the first time. A key to all known species of Mexican Orthocentrus is provided and distribution maps are presented.